KETERAMPILAN MEMBUAT BATIK JUMPUTAN DENGAN METODE ACTIVE LEARNING TIPE SMALL GROUP WORK SISWA AUTIS - CHRISTI ANGGER KINASIH, AGITHA (Jurnal Pendidikan Khusus, 2016)
ABSTRACT This research purpose was to describe the skill of making jumputan batik using Active Learning of Small Group Work Type to autism children in Sidoarjo. This research was done in 8 times meeting. The data collection technique used the test of work demonstration assessment and the result observation. The approach used was descriptive quantitative with the data analysis of descriptive statistic used percentage method. This research result indicated that from 13 research subjects, all of them could do the skill of jumputan batik well. On the first meeting the average value of 13 students was 61 or 61% doing jumputan batik activity was implemented well. The value enhanced till the eighth meeting, the average value reached 88 or 88% doing jumputan batik activity was implemented well.   Keywords:  batik, Active Learning of Small Group Work Type